Bahasa Inggris - Putu Gde Hari Wangsa; I Gde Nengah Adhilaksman S.W; Ni Nyoman Ayu Sutrini (WMJ (Warmadewa Medical Journal), 2025)
Vitiligo is a pigmentation disorder characterized by hypopigmented macules resulting from the chronic and progressive loss of epidermal melanocyte function. This condition creates a stark contrast between depigmented and normal skin, which can be distressing for patients, particularly from a cosmetic perspective. Consequently, individuals with vitiligo often face stigmatization and psychosocial challenges, making them more susceptible to depression, anxiety, and stress. The treatment of vitiligo should also address its emotional impact, ultimately facilitating better adaptation to the disease and improving the patient's quality of life. This study aims to examine the relationship between vitiligo severity, measured using the Vitiligo Area Scoring Index (VASI), and the Dermatology Life Quality Index (DLQI). It employs an analytical cross-sectional approach involving vitiligo patients treated at Bali Mandara General Hospital. Primary data were collected through clinical assessments of VASI scores, followed by the completion of the validated and reliable DLQI questionnaire. The results indicate that the degree of depigmentation in vitiligo (VASI) has a strong impact on patients' quality of life (DLQI). Further research is needed to assess changes in DLQI after vitiligo patients undergo phototherapy or topical treatment, as well as to identify other factors beyond VASI that influence DLQI.